PENGARUH PUNISHMENT DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA IV REGIONAL I MEDAN - Devita, Tiara; Sahputra, Ngatno; Rahim, Rani (Journal Economic Management and Business, 2025)
This research aims to determine the effect of punishment and career development on employee performance at PT. Perkebunan Nusantara IV Regional I Medan. A quantitative method was used, and data collection techniques included observation, interviews, questionnaires, and documentation. The results showed that both punishment and career development had significant partial and simultaneous effects on employee performance. The coefficient of determination (R²) reached 0.795, indicating that 79.5% of employee performance variation could be explained by the two variables.